Kulturowy model niepełnosprawności wyzwaniem dla pedagogiki specjalnej - Twardowski, Andrzej (Studia Edukacyjne, 2023)
The aim of the article is to present the cultural model of disability and its consequences for special education. I will start by presenting the origins and essence of the cultural model of disability. Next, I will characterize the four main assumptions underlying this model: 1) disability can be understood differently in different cultures, 2) people perceive disability through the prism of the experiences they have acquired in their culture, 3) the understanding of disability depends on the type of discourse that constitutes its meaning, 4) the commonly unquestionable “efficiency” usually referred to as “normality” should be questioned. In the second part of the article, I will discuss the most important implications of the cultural model of disability for the theory and practice of special education.